KNOWLEDGE AND PERCEPTIONS OF DIABETES IN URBAN AND SEMI URBAN POPULATION OF PESHAWAR, PAKISTAN - Zuhaid, Muhammad; Zahir, Khalil Khan; Diju, Inayat Ullah (Journal of Ayub Medical College Abbottabad, 2012)
Background: Diabetes mellitus is a major health issue in Pakistan. The aim of this study was to evaluate the knowledge and perceptions of diabetes in a sample population of Peshawar. Methods: This crosssectional, descriptive study was carried out in seven different localities of Peshawar. A sample of 305 residents were interviewed aged from 15-60 years and above, using a questionnaire specifically designed and translated into Urdu language for convenience of selected subjects. Results: Knowledge of diabetes was suboptimal. The mean percentages of correct responses to questions regarding three classical symptoms and given complications were 47.1% and 30.8%. Excessive sugar intake, obesity, family history, lack of physical activities and stress were acknowledged by 46.2%, 42.3%, 39.3%, 33.4%, and 31.8% of the subjects respectively. Presence of family history and level of education were recognised to be associated with more knowledge. Conclusion: There is lack of awareness of major risk factors and some complications of diabetes mellitus. Level of education is a significant predictor regarding knowledge of diabetes and its prevention. Prevalence of diabetes has increased in Pakistan. Keywords: Diabetes, Knowledge, Perceptions, Peshawar